Pengaruh Struktur Pasar, Bank Size, Inflasi dan Gross Domestic Product Terhadap Kinerja Bank di ASEAN 5 (Studi Kasus Bank Komersial di ASEAN 5 Periode Tahun 2007-2014) - Ajeng K, Eka; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to analyze some factors which affect of Return On Asset Banks as Market Structure, Bank Size, Inflation and Gross Domestic Product (GDP). This study uses secondary data from 25 banks annual report, change of inflation and GDPÂ ASEAN 5, those are: Indonesia, Malaysia, Singapore, Philipina and Thailand in years period 2007 to 2014. The sampling method used Purposive Sampling based on a country with banks released a financial report financial. Data analysis used a panel data regression test that was a combination of data cross section and time series with fixed effect model. The results of test found that in partial market structure which is measured using Herfindahl Hirschman Index and GDP have a positive and significant impact. While bank size and inflation do not affect significantly on ROA (Return On Assets)